Cerai Talak dengan Alasan Virginitas dalam Tinjauan Hukum Islam dan Feminisme (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This article is intended to explain the views of Islamic law and feminism on the phenomenon of divorce on the grounds that his wife was not a virgin from the start of her marriage. This research uses a doctrinal legal research approach as well as jurisprudence feminism. Data sources related to doctrinal legal research are in the form of Islamic legal norms contained in the treasures of fiqh, as well as fiqh which has been made into positive law in the form of the Marriage Law and Compilation of Islamic Law. The data source for the feminist jurisprudence approach is in the form of observations on the phenomenon of the rise of divorce cases in the Religious Courts on the grounds that the wife was not virgin before marriage. The results of the study show that there are similarities and differences in Islamic law and feminism in terms of virginity. In terms of similarities, both of them view that virginity is not always measured by the integrity of the hymen, but it is necessary to distinguish between sexual and non-sexual factors. However, from the other side, Islam views that a husband has the right to know about his wife's virginity from the start of marriage, whereas according to feminism a wife has the right to keep this secret. Divorce on the grounds of virginity can already meet the legal-formal fair criteria, but not morally.